Concepts, Classification, and Product Development Strategies in Modern Marketing: A Literature Review - Binda Rahma Cahyani; Mifta Hasda; Muhammad Syaipudin (Global Sustainability Research Institute, 2026)
This article discusses the concept and classification of products as an important part of marketing activities and business development. A product is anything that can be offered to the market to satisfy consumer needs and wants, whether in the form of goods or services. In the business world, understanding product concepts is essential for companies to create value and customer satisfaction. The discussion in this article includes the definition of products, product levels, and various product classifications based on durability, usage, and consumer characteristics. In addition, this article explains the importance of product development strategies in facing increasingly competitive market conditions. The method used in writing this article is a literature study by collecting various sources from books, journals, and scientific references related to marketing management. The results show that product classification helps companies determine appropriate marketing strategies, including pricing, promotion, distribution, and market segmentation. By understanding product concepts and classifications comprehensively, companies can improve product quality and maintain long-term customer loyalty.